Diagnostic and therapeutic pitfalls in the management of pediatric patients with 3β-hydroxysteroid dehydrogenase type 2 (3β-HSD2) deficiency - a single center experience - Gawlik, Zuzanna; Preizner-Rzucidło, Ewelina; Kaleta, Konrad; Szwarkowska, Maria; Wróblewska, Martyna; Jurek, Aleksandra; Książek, Teofila; Jażdżewski, Krystian; Siejka, Anna; Starzyk, Jerzy; Januś, Dominika (Frontiers in Endocrinology, 2025)
IntroductionCongenital adrenal hyperplasia (CAH) due to 3β-hydroxysteroid dehydrogenase type 2 deficiency (3β-HSD2D) is an exceptionally rare disorder affecting adrenal steroidogenesis, leading to variable clinical presentations. This study aims to highlight the phenotypic variability and management challenges associated with 3β-HSD2D through the analysis of three pediatric cases.MethodsWe retrospectively reviewed three patients diagnosed with 3β-HSD2D at the Pediatric Endocrinology Department of the University Children’s Hospital in Krakow. Clinical features, laboratory findings, genetic analyses, and management strategies were evaluated. A detailed literature overview has been performed to find previously described 3β-HSD2D patients and correlate clinical presentation with distinct variants in the HSD3B2 gene.ResultsCase 1: A female neonate presented with adrenal insufficiency, electrolyte imbalances, hyperpigmentation, and congenital heart defects. Genetic testing revealed a homozygous missense pathogenic variant c.760T>G (p.Tyr254Asp) in the HSD3B2 gene. Hydrocortisone and fludrocortisone therapy was introduced in the 2nd week of life. Case 2: A male infant exhibited atypical genitalia without salt-wasting crises. Compound heterozygous pathogenic variants c.760T>G (p.Tyr254Asp) and c.308-6G>A in HSD3B2 gene were identified. He received therapy with testosterone prior to hypospadias correction and started therapy with hydrocortisone at the age of 1 y 10 m due to increased growth velocity and acceleration of bone age. Case 3: A female infant with salt-wasting crises and virilization was diagnosed with 3β-HSD2D. She additionally developed polycystic kidney disease, gallbladder stones and ovarian cysts. A pathogenic c.849del variant in homozygosity in HSD3B2 was detected.ConclusionsThis work underscores the clinical heterogeneity of 3β-HSD2D and the necessity for comprehensive genetic evaluation. Variants in the HSD3B2 gene contribute to diverse phenotypes, complicating diagnosis and management. Retrospective evaluation of previously described cases offers us guidelines in the management of patients, who need multidisciplinary care involving endocrinology, genetic, gynecology, and urology specialists.